Human Resource Management Practices of School Heads in City Schools Division Office of Antipolo - Balajadia, Shaharah Mae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the human resource management (HRM) practices employed by public elementary school heads in District II-A, City Schools Division of Antipolo during School Year 2025–2026. Specifically, it described the profile of school heads and teachers, determined the extent of HRM practices in terms of recruitment and selection, training and development, performance management, and employee relations, and analyzed significant differences based on respondents’ profiles. A descriptive research design was utilized, using a researcher-made questionnaire-checklist as the primary data-gathering instrument. The respondents consisted of six school heads and 153 teachers from six elementary schools, selected through stratified random sampling, representing 22% of the total population.Findings revealed that most school heads were aged 46 years and above with higher academic qualifications, while most teachers were aged 31–35 years with Master’s degrees. School heads generally held higher positions and longer years of service compared to teachers. In terms of HRM practices, both groups rated training and development as the most evident practice, followed by recruitment and selection and performance management, while employee relations was rated the lowest but still evident. Statistical analysis showed that educational attainment significantly influenced perceptions of HRM practices, particularly in recruitment, training, and performance management, while position title significantly affected perceptions of training and development. Other demographic variables showed no significant effect.The study concludes that educational attainment and leadership position are key determinants of HRM perceptions among school heads, highlighting the importance of professional qualification in effective human resource implementation. It further emphasizes the need for inclusive, flexible, and responsive HRM policies that consider individual differences among school personnel.It is recommended that school heads strengthen training programs, promote fairness and transparency in HR processes, enhance workplace relationships through collaboration and feedback mechanisms, and support leadership development through on-the-job training. Future studies may explore additional variables to further enrich understanding of HRM practices in educational settings.